1998
DOI: 10.1084/jem.187.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous Presentation and Recognition of Nucleosomal Autoepitopes in Lupus: Role of Autoimmune T Cell Receptor α Chain

Abstract: T cells specific for nucleosomal autoepitopes are selectively expanded in lupus mice and these Th cells drive autoimmune B cells to produce pathogenic antinuclear antibodies. We transfected the TCR-α and -β chain genes of a representative, pathogenic autoantibody-inducing Th clone specific for the nucleosomal core histone peptide H471–94 into TCR-negative recipient cells. Although the autoimmune TCRs were originally derived from SNF1 (I-Ad/q) mice, the transfectants could recognize the nucleosomal autoepitope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 55 publications
5
87
0
Order By: Relevance
“…Consistently, we also observed that in chronic graft versus host disease (GVHD) recipients, there were alloreactive CD4 + T clones that possess autoreactivity and mediate autoimmune-like chronic GVHD (41). Our observations are also consistent with others' reports that autoreactive or alloreactive T cells can express promiscuous TCRs that are capable of responding to more than one Ag (13,(42)(43)(44)(45). In addition, recent reports indicate that some autoreactive T cells can express more than one TCR as a means of surviving thymic negative selection (46).…”
Section: Discussionsupporting
confidence: 81%
“…Consistently, we also observed that in chronic graft versus host disease (GVHD) recipients, there were alloreactive CD4 + T clones that possess autoreactivity and mediate autoimmune-like chronic GVHD (41). Our observations are also consistent with others' reports that autoreactive or alloreactive T cells can express promiscuous TCRs that are capable of responding to more than one Ag (13,(42)(43)(44)(45). In addition, recent reports indicate that some autoreactive T cells can express more than one TCR as a means of surviving thymic negative selection (46).…”
Section: Discussionsupporting
confidence: 81%
“…The therapeutic benefit of H4 71-94 peptide is further augmented by degeneracy of lupus autoimmune system for nucleosomal epitopes: a single peptide epitope from a histone in the nucleosome can be recognized by multiple autoimmune T cells of lupus with diverse receptors, and conversely, a single autoimmune T cell can recognize structurally different histone peptides (12,14). Thus, a single peptide epitope can tolerize a spectrum of autoimmune Th cells and tolerizing one set of Th cells deprives help for multiple autoimmune B cells of lupus (tolerance spreading) (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…Certain peptides in nucleosomal histones are dominant autoepitopes and spontaneous priming to these occurs in preclinical lupus (12,13). These epitopes are cross-reactively recognized by autoimmune Th cells, as well as B cells of lupus, and they can be promiscuously presented in the context of diverse MHC class II (MHC II) 4 alleles, like "universal epitopes" (2,(12)(13)(14). These unaltered, native peptide epitopes halt progression of lupus nephritis upon tolerization in high-dose soluble form and importantly for human therapy, the peptides are also effective in delaying/preventing lupus nephritis in subnanomolar doses (ϳ0.37 nM or 1 g), administered s.c. to lupus-prone SNF 1 mice (2,3,15).…”
Section: Low-dose Peptide Tolerance Therapy Of Lupus Generates Plasmamentioning
confidence: 99%
“…In subsequent steps, the B cells present novel self determinants for a second tier of T-cell priming and finally, T cells provide help for a diversified B-cell response. This mechanism of collaboration between T and B cells specific for antigens noncovalently linked in a particle (also termed intermolecular-intrastructural help) might play an important role in the case of autoimmune response to chromatin [25,26]. It has been proposed that ab T-cell receptor bearing T cells specific for nucleosomal peptides are implicated in the production of anti-DNA antibodies.…”
Section: Linked Sets Of Autoantibodies In Nonorgan (Systemic) Autoimmmentioning
confidence: 99%